Mediating effect of sleep quality on relationship between job stress and mental health status among occupational population - Mengting LIU; Li NING; Xiaoyan GAO (环境与职业医学)
BackgroundIn the context of the innovation-driven development strategy, occupational groups are facing increasing work pressure, and its impact on sleep quality and mental health deserves attention.ObjectiveTo explore potential mediating role of sleep quality between work stress and mental health status among occupational workers, and to provide a scientific basis for improving their mental health status. MethodsCluster sampling was used to select 2000 workers in Urumqi, Xinjiang Uygur Autonomous Region. They were divided into mental and physical worker groups according to their occupational types, and a questionnaire survey was conducted using General Information Survey Forms, Effort Reward Imbalance scale (ERI), Pittsburgh Sleep Quality Index (PSQI), and Symptom Check List-90 (SCL-90). Work stress level, sleep quality, and mental health were assessed and compared between mental and physical workers. Structural equation modelling was used to evaluate the relationship among work stress, sleep quality and mental health of the workers, and to explore the mediating effect of sleep quality. ResultsA total of 1979 survey questionnaires were collected, with a response rate of 99%, including 1500 (75.8%) mental workers and 479 (24.2%) physical workers. Linear correlations were confirmed between work stress, mental health, and sleep quality. The correlations of work stress with mental health and sleep quality scale scores were positive for both mental and physical workers (r=0.32, 0.31, P<0.01; r=0.25, 0.25, P<0.01), and sleep quality was also positively correlated with mental health (r=0.47, 0.56, P<0.01) . The final modified structural equation model showed that the coefficients of work stress on sleep quality for the mental and physical workers were 0.56 and 0.46 (P<0.001) respectively, and the coefficients of sleep quality on mental health were 0.52 and 0.80 (P<0.001) respectively. Sleep quality mediated the impact of work stress on mental health of the mental and physical workers, with mediating effect values of 0.29 and 0.37 respectively. The adaptability of both structural equation models is less than 3. ConclusionOccupational population's work stress and mental health may be mediated by sleep quality, and measures should be taken to reduce work stress and improve sleep quality and mental health.